Embryological features and bacterial transmission to gynoecium and ovule in Myrsine laetevirens (Myrsinaceae) - Otegui, Marisa Silvina (1998)
Fil: Otegui, Marisa Silvina. Instituto de Fisiología Vegetal (INFIVE). Facultad de Ciencias Naturales y Museo. Universidad Nacional de La Plata; Argentina